Silverado - Kasdan, Lawrence, 1949-.; Williams, Brad, 1984-; Danny Glover; Kevin Costner; Marvin J McIntyre; Scott Glenn; Sheb Wooley; Kevin Kline (USA Columbia Pictures Corporation, 1985)
In 1880, four men travel together to the city of Silverado. They come across with many dangers before they finally engage the ""bad guys"" and bring peace and equality back to the city.
A misfit bunch of friends come together to right the injustices which exist in a small town.
Lawrence Kasdan
Language(s): English, French, Italian
Subtitle(s): English, French, Italian, Arabic,Hebrew, Hindi, Icelandic, Turkish
Keywords: Comedy; Western; Action